Inclusive Participatory Public Administration: Marginalized Communities along Karang Mumus River, Samarinda - Paselle, Enos; Waldianto, Wendy; Erika Bato, Bulan (Iapa Proceedings Conference, 2025)
This study explores the experiences of riverside residents along the Karang Mumus River (SKM) in facing revitalization and relocation processes, and analyzes the extent to which the SKM revitalization policy has adopted participatory and inclusive principles of public administration. It also aims to construct a context- based conceptual model of inclusive public administration that integrates the protection of basic rights, deliberative participation, and multi-actor collaboration. Using an interpretive qualitative approach and an exploratory case study method, the research maps the experiences of marginalized residents during the planning and implementation phases of the revitalization program, which directly affect their right to housing, livelihoods, and access to basic services. The findings reveal that public participation tends to be formalistic, protection of residents’ rights remains limited, and while NGOs and academics are actively involved, their roles are still fragmented. This study concludes that an inclusive model of public administration must simultaneously integrate three critical pillars: the protection of socio-economic rights, meaningful deliberative participation, and the facilitation of collaborative dialogue among policy actors. The novelty of this research lies in the formulation of the Three Pillars of Inclusivity Model, which serves as a conceptual framework for achieving socially just and community-rooted policy governance.